PENGARUH KOMPETENSI, MOTIVASI DAN LINGKUNGAN KERJA TERHADAP KINERJA PEGAWAI DI KANTOR PENCARIAN DAN PERTOLONGAN SEMARANG - Rr. Dian Indra Kusumasari; Fitri Lukiastuti (Magisma: Jurnal Ilmiah Ekonomi dan Bisnis, 2020)
This study aims to determine how much influence the competence, motivation and work environment on the performance of employees in Semarang search and help offices, both partially and simultaneously. The population in this study were all members of the Semarang search and rescue office as many as 122 employees. The sampling technique uses census. The data used in this study are primary and secondary data, then proceed with multiple linear regression analysis with the help of the SPSS 18 program. The results of the analysis show that Competence has a significant positive effect on the performance of Semarang Search and Relief Office employees both partially and simultaneously. Motivation significant positive effect on the performance of Semarang Search and Relief Office employees both partially and simultaneously, and the work environment significantly positive effect on the performance of Semarang Search and Relief Office employees both partially and simultaneously